2023
DOI: 10.3390/ma16217014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyoxymethylene Fiber on the Mechanical Properties and Abrasion Resistance of Ultra-High-Performance Concrete

Lixin Tan,
Jun Yang,
Chuanxi Li
et al.

Abstract: It is necessary to prepare marine UHPC with synthetic fibers instead of steel fibers, owing to the corrosion risk of steel fibers in marine environments. Currently, the performance of UHPC prepared with different types of fibers has not been comparatively investigated. This work prepared UHPC with steel fiber, polyoxymethylene (POM) fiber, polypropylene (PP) fiber, and polyvinyl alcohol (PVA) fiber. The effects of different fibers on the mechanical properties, impact, and abrasion resistance of UHPC were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The slump flow of UHPFRC of 723 mm satisfied the target value of 700 ± 100 mm. The performance was considered appropriate considering previous literature [49,50].…”
Section: Materials Used and MIX Proportionmentioning
confidence: 99%
“…The slump flow of UHPFRC of 723 mm satisfied the target value of 700 ± 100 mm. The performance was considered appropriate considering previous literature [49,50].…”
Section: Materials Used and MIX Proportionmentioning
confidence: 99%
“…Studies have found that adding fibers can effectively improve the fracture toughness and cracking behavior after the bending of building materials [4][5][6]. The main principles are debonding, slipping, and pulling out between the fibers and the matrix, as well as the impact of the fracture of the fiber body on external energy.…”
Section: Introductionmentioning
confidence: 99%